Effects of high temperature stress on the intestinal histology and microbiota in Yesso scallop Patinopecten yessoensis. (March 2023) - Kong, Ning; Zhao, Junyan; Zhao, Bao; Liu, Jinyu; Li, Fuzhe; Wang, Lingling; Song, Linsheng
Abstract: High temperature stress posed by global warming is considered as one of the greatest threats to marine ectotherms by altering their behavior and physiological functions. The intestine and its associated microbiota constitute the first defensive line for the animals against environmental stresses, but their responses to high temperature stress in mollusks are largely unknown. In the present study, the changes of intestinal histology and microbiota were investigated in Yesso scallop Patinopecten yessoensis, a cold-water bivalve species, after high temperature stress. The shrinkage of intestinal lumen, shortening of intestinal villi and increased goblet cells were observed in the intestines of scallops exposed to seawater temperatures of 20 °C (T20 group) and 23 °C (T23 group), compared to the control group (15 °C). High-throughput sequencing of 16S rRNA gene showed that the composition of intestinal microbiota rather than the alpha diversity indices changed significantly after high temperature stress. At the phylum level, the relative abundances of Proteobacteria and Firmicutes decreased progressively with increasing temperature, while that of Bacteroidetes increased by 1.18-fold in the T20 group and 0.95-fold in the T23 group. At the genus level, Tenacibaculum and Mycoplasma were significantly enriched after high temperature stress, and Mycoplasma exhibited highest abundance of 39.43% in the T23 group. Functional prediction revealed that the pathways related to amino acid biosynthesis were blocked after high temperature stress, while that of phospholipases showed the opposite trend. According to the results of network analysis, the network connectivity decreased with increasing temperature, while the percentages of negative correlations in the two high temperature groups were higher than that in the control group. Collectively, the intestinal histology and microbial community of P . yessoensis changed significantly after high temperature stress, which would hinder the nutrient absorption and promote the proliferation of pathogenic microorganisms in the intestine of scallops. Our results will provide novel insights into the occurrence mechanism of mass summer mortality in marine mollusks. Highlights: High temperature stress (HS) led to histological changes in the scallop intestine. HS altered the composition and function of the intestinal microbial community. Tenacibaculum and Mycoplasma were significantly enriched after HS. The connectivity of microbial network decreased with increasing temperature.